Annotated checklist of millipede of the infraclass Pentazonia (Myriapoda: Diplopoda) of Indonesia: Pill millipedes from Indonesia - Anh, Nguyen Duc; Eguchi, Katsuyuki; Sierwald, Petra (Academia Journal of Biology, 2023)
A comprehensive checklist of millipedes of the infraclass Pentazonia is compiled for Indonesia. A total of 80 species assigned to 11 genera, three families and three orders has so far been recorded. Two genera are remarkably species-rich: Castanotherium (36 species) and Hyleoglomeris (15 species). Three genera, Malayomeris, Rajasphaera, Leptoprotopus are monotypic. Most of the species are endemic, recorded only in Indonesia (71 species).